Remembrance of Bob Jahn - Edwards, Tony (Journal of Scientific Exploration, 2018)
As a BBC television producer with a (wholly unauthorised and sub rosa) personal mission to inform the public of breakthrough discoveries rejected by the scientific establishment, my ears pricked up at the jungle drums coming from Princeton in the early 1980s. I had long wanted to make a program about ESP research, and it was Bob’s data and academic status that helped convince my skeptical BBC bosses that it was high time Horizon (and its US sister Nova) took a look at the subject. At the time, however, Bob was still Dean of the Faculty of Engineering, and, despite receiving a suitably effusive written invitation, he declined to take part. His reply was diplomatic, wishing me well with the TV program, but enabling me to read between the lines that he been sat upon by the Princeton authorities. However, I did sneak in a reference to Bob in the final BBC program The Case of ESP [https://youtu.be/h2Gog3xMluA] . I finally “nailed” Bob televisually in 1993, when he agreed to be one of the candidates in my 6-part BBC series about dissident scientists. Called Heretic, the series also featured Linus Pauling, Rupert Sheldrake, Jacques Benveniste, Eric Laithwaite, and Hans Eysenck. Bob had by then been demoted from Dean, whereupon the University removed the publicity shackles, evidently deeming its reputation less vulnerable to the deranged research interests of a mere Professor. Heretic: Robert Jahn (1994) can be viewed on YouTube at <a href="/index.php/jse/author/submit/As%20a%20BBC%20television%20producer%20with%20a%20(wholly%20unauthorised%20and%20sub%20rosa)%20personal%20mission%20to%20inform%20the%20public%20of%20breakthrough%20discoveries%20rejected%20by%20the%20scientific%20establishment,%20my%20ears%20pricked%20up%20at%20the%20jungle%20drums%20coming%20from%20Princeton%20in%20the%20early%201980s.%20I%20had%20long%20wanted%20to%20make%20a%20program%20about%20ESP%20research,%20and%20it%20was%20Bob’s%20data%20and%20academic%20status%20that%20helped%20convince%20my%20skeptical%20%20BBC%20bosses%20that%20it%20was%20high%20time%20Horizon%20(and%20its%20US%20sister%20Nova)%20%20took%20a%20look%20at%20the%20subject.%20%20At%20the%20time,%20however,%20Bob%20was%20still%20Dean%20of%20the%20Faculty%20of%20Engineering,%20and,%20despite%20receiving%20a%20suitably%20effusive%20written%20invitation,%20he%20declined%20to%20take%20part.%20His%20reply%20was%20diplomatic,%20wishing%20me%20well%20with%20the%20TV%20program,%20but%20enabling%20me%20to%20read%20between%20the%20lines%20that%20he%20been%20sat%20upon%20by%20the%20Princeton%20authorities.%20However,%20I%20did%20sneak%20in%20a%20reference%20to%20Bob%20in%20the%20final%20BBC%20program%20The%20Case%20of%20ESP%20[https:/youtu.be/h2Gog3xMluA]%20.%20I%20finally%20“nailed”%20Bob%20televisually%20in%201993,%20when%20he%20agreed%20to%20be%20one%20of%20the%20candidates%20in%20my%206-part%20BBC%20series%20about%20dissident%20scientists.%20Called%20Heretic,%20the%20series%20also%20featured%20Linus%20Pauling,%20Rupert%20Sheldrake,%20Jacques%20Benveniste,%20Eric%20Laithwaite,%20and%20Hans%20Eysenck.%20%20Bob%20had%20by%20then%20been%20demoted%20from%20Dean,%20whereupon%20the%20University%20removed%20the%20publicity%20shackles,%20evidently%20deeming%20its%20reputation%20less%20vulnerable%20to%20the%20deranged%20research%20interests%20of%20a%20mere%20Professor.%20Heretic:%20Robert%20Jahn%20(1994)%20can%20be%20viewed%20on%20YouTube%20at%20https:/youtu.be/8A6pPLEzkhg%20">https://youtu.be/8A6pPLEzkhg